Financial well-being among Malaysian manufacturing employees - Shiau, Wei Chan; Omar, Siti Sarah; Wen, Lik Yong (Growing Science, 2018)
Employees and financial well-being are two aspects that are closely related to each other, and have been deeply studied by researchers. Not only can financial well-being directly affect an individual, but it can also indirectly affect his/her organization as well as employer. Any level of financial employees’ well-being, either low or high, will change their job performance. Thus, the purpose of this study is to determine the level of financial well-being among manufacturing employees in Batu Pahat, as well as to test the relationships between determinants and financial well-being among manufacturing employees in Batu Pahat. In this study, seven research hypotheses were developed to examine seven determinants, including age, income, gender, education, current job position, income, and marital status which influence employees‘ financial well-being. In this study, 220 employees at the production level were selected randomly from a manufacturing company in Batu Pahat, Johor, Malaysia. Then, a questionnaire was distributed to the employees. The data obtained were analyzed quantitatively using SPSS version 22.0. The results of this study revealed that the level of financial well-being was moderate and all of the determinants were positively related to financial well-being among the manufacturing employees. This quantitative study is important to the manufacturing industry in Malaysia in order to gain insight on the correlation between financial well-being and its determinants.